The effects of crime on the retail business sector in the Matjhabeng, Free State - de Lange, Joel Johannes (Bloemfontein: Central University of Technology, Free State, 2014)
Mathjabeng is a Sesotho word meaning "where nations meet," and is centrally located in the Free State and South Africa. Mathjabeng Municipality consists of the following towns: Welkom, Virginia, Odendaalsrus, Allanridge, Ventersburg and Hennenman,
Thesis
Keywords: Retail trade - South Africa - Security measures; Shoplifting - South Africa - Free State Province; Business losses